2019
DOI: 10.1002/ep.13230
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soil Organic Matter, Electrical Conductivity and Acidity on the Soil's Carbon Sequestration Ability Via Two Species of Tamarisk (TamarixSpp.)

Abstract: Carbon sequestration constitutes a part of the carbon cycle. It is a term used for describing carbon exchange with the environment. This study was conducted to evaluate how soil organic matter and other related parameters affect carbon sequestration in the soil via the presence of two plants Tamarix aphylla and Tamarix kotschyi. Two ranges of depth (0–15 and 15–30 cm) were studied in the soil. This study was carried out in two separate factorial experiments using a randomized complete design (RCD) with three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Soil organic matter (SOM) contributes to soil fertility and crop growth by numerous ways such as the binding and buffering of plant nutrients (Murphy, 2015), providing habitat and food for soil organisms (Sapkota et al, 2012;Aldebron et al, 2020), maintaining soil moisture (Lipiec et al, 2006) and improving the soil structure (Masri & Ryan, 2006;Simansky et al, 2013). Besides these functions, SOM is a form of carbon sequestration and is therefore important for mitigating greenhouse gas emissions (Lal, 2004;Iranmanesh & Sadeghi, 2019). Organic matter (OM) is added to the soil by organic manures and crop residues and leaves the soil by mineralization due to decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Soil organic matter (SOM) contributes to soil fertility and crop growth by numerous ways such as the binding and buffering of plant nutrients (Murphy, 2015), providing habitat and food for soil organisms (Sapkota et al, 2012;Aldebron et al, 2020), maintaining soil moisture (Lipiec et al, 2006) and improving the soil structure (Masri & Ryan, 2006;Simansky et al, 2013). Besides these functions, SOM is a form of carbon sequestration and is therefore important for mitigating greenhouse gas emissions (Lal, 2004;Iranmanesh & Sadeghi, 2019). Organic matter (OM) is added to the soil by organic manures and crop residues and leaves the soil by mineralization due to decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly the correlation between OM and K is expected as an increase in OM increase the CEC of soils, making K fixation higher (Weil and Brady, 2017). The correlation between OM and ECe dS/m is interesting as an increase in ECe dS/m directly reduces the decomposition of OM in the soil (Iranmanesh and Sadeghi 2019). A decrease in OM decomposition will also result in a decrease of available P which further explains the results in Table 3.…”
Section: Soil Analysismentioning
confidence: 66%
“…It has been reported that a slight increase in pH is beneficial for supporting plant diversity which might have a positive impact on SOC (Zhang et al 2021). Also, EC is an important parameter to be studied in SOC studies as both very high and very low values of EC cause reduced growth of plants in a way affecting the SOC (Iranmanesh and Sadeghi 2019;Stadler et al 2015).…”
Section: Methodsmentioning
confidence: 99%